Did Socrates intend to commit suicide? A rereading of the defense of Socrates in Xenophon's Apology: ¿Tenía Sócrates la intención de suicidarse? Una relectura de la defensa de Sócrates en la Apología de Jenofonte - Dorion, Louis-André (Araucaria, 2024)
In recent years, several commentators have argued that Socrates, at the time of his trial, intended to die, and that he therefore used megalêgoria ("boasting") to provoke his judges into condemning him to death. Contrary to this reading of the Apology, I shall endeavor to show that Socrates actually defends himself during his trial, and that the intention behind his choice of megalêgoria is not to provoke his judges into condemning him to death.